A Detailed Photometric Analysis of Early-Type Spiral Galaxies in Pairs - Gorsuch, Miranda R (Proceedings of the Wisconsin Space Conference, 2023)
This project explores the relative role of “nature versus nurture” (intrinsically versus environmentally driven influences) in shaping the morphology and evolution of galaxies by performing a detailed photometric analysis of early-type spiral galaxies found in galaxy pairs. We use Fourier analysis to model the properties of the spiral arms and bulge/disk/bar decomposition analysis to find the properties of the bulge, disk, and bar of each spiral galaxy within our sample. We investigate the effect environmental density has on the formation and evolution of early-type galaxies by comparing our results with previous work done for samples of early-type galaxies found in different environments (isolated and loose groups). This analysis will allow us to gain more insight into the formation and evolution of spiral galaxies across a range of environments.